FRI0413 Acute effect of iloprost on peripheral circulation as assessed by videocapillaroscopy and 22-mhz power doppler ultrasonography. (15th June 2017) - Schioppo, T; Orenti, A; Boracchi, P; Lucia, O De; Murgo, A; Meroni, PL; Ingegnoli, F; ,
Abstract : Background: Vascular involvement is a hallmark of systemic sclerosis (SSc) and it is responsible for some of the most common complications of the disease such as Raynaud's phenomenon (Rp), digital ulcers (DUs) and pulmonary arterial hypertension. I.V. iloprost (ILO), a prostacyclin analogue, has been shown to be effective in reducing Rp severity, DUs healing and preventing [1]. Objectives: To assess the acute effect of ILO on acral circulation as assessed by nailfold videocapillaroscopy (NVC) and 22-MHz Power Doppler ultrasound (PDUS). Methods: 44 SSc consecutive patients fulfilling the 2013 EULAR classification criteria were enrolled. Each patient was evaluated before and immediately after I.V. ILO administration (0.5–2.0 ng/Kg/min for 6 consecutive hours). PDUS was performed at the 3rd and 4th finger of the dominant hand after exclusion of ulnar artery occlusion (UAO). In case of UAO non-dominant hand was examined. Ultrasound investigation was performed with Esaote MyLab 70 XVG by means of linear array transducer (10–22 MHz). Power Doppler settings were standardized (Doppler frequency 14.3 MHz, Gain 55%, PRF 750 Hz). PDUS measurements included sagittal scan of nailbed and fingertip qualitatively graded from 1 (no signal) to 4 (marked hyperemia) [2], and resistivity index (RI) of ulnar and radial proper digital arteries. Capillary width (sum of capillary width/mm) was calculated by NVC with magnification 200X performed on two images of the same digits examined by PDUS. Results: The study population included 44 SSc patients, 40 (90.9%) women, 35 (79.5%) limited cutaneous SSc, median age 60.2 years old and median disease duration 8 years. 19 (43.2%) had history of DUs, among them 15 had experienced more than one DUs and 1 had active DU at the moment of evaluation. Semiquantitative perfusion score of sagittal scan of nailbed and fingertip pre- and post-therapy are shown in Table 1 . Changes in RI and capillary width pre- and post-infusion are reported in Table 2. Conclusions: A statistically significant post-infusion rise in RI, fingertip and nailbed PDUS grade were found. Capillary width was also increased, but it was not statistically significant. As such, these novel results indicate that ILO, alongside its clinical effect, is able to enhance vascularization even at the most peripheral levels. References: Pope J et al. Cochrane Database Syst Rev. 2000;(2):CD000953. Newman JS et al. Radiology. 1996, 198:582–584. Disclosure of Interest: None declared